2019
DOI: 10.1016/j.molcel.2018.11.018
|View full text |Cite
|
Sign up to set email alerts
|

The Crohn’s Disease Risk Factor IRGM Limits NLRP3 Inflammasome Activation by Impeding Its Assembly and by Mediating Its Selective Autophagy

Abstract: Summary Several large-scale genome-wide association studies genetically linked IRGM to Crohn’s disease and other inflammatory disorders in which the IRGM appears to have a protective function. However, the mechanism by which IRGM accomplishes this anti-inflammatory role remains unclear. Here, we reveal that IRGM/Irgm1 is a negative regulator of the NLRP3 inflammasome activation. We show that IRGM expression, which is increased by PAMPs, DAMPs, and microbes, can suppress the pro-inflammatory responses provoked … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
173
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 166 publications
(188 citation statements)
references
References 51 publications
7
173
0
Order By: Relevance
“…Activations of these pathways lead to robust induction of interferon response resulting in antiviral response or autoimmune diseases (Gkirtzimanaki et al, 2018;Sliter et al, 2018;Tal et al, 2009;Xu et al, 2019). Others and we have found that IRGM is a key autophagy protein that plays a significant role in anti-bacterial autophagy and autophagy of inflammasomes (Chauhan et al, 2015;Kumar et al, 2018;Mehto et al, 2019;Singh et al, 2006;Singh et al, 2010). IRGM was also shown to present over mitochondria, and overexpression of IRGM induces mitochondrial fission, followed by its depolarization (Singh et al, 2010).…”
Section: Introductionmentioning
confidence: 81%
See 4 more Smart Citations
“…Activations of these pathways lead to robust induction of interferon response resulting in antiviral response or autoimmune diseases (Gkirtzimanaki et al, 2018;Sliter et al, 2018;Tal et al, 2009;Xu et al, 2019). Others and we have found that IRGM is a key autophagy protein that plays a significant role in anti-bacterial autophagy and autophagy of inflammasomes (Chauhan et al, 2015;Kumar et al, 2018;Mehto et al, 2019;Singh et al, 2006;Singh et al, 2010). IRGM was also shown to present over mitochondria, and overexpression of IRGM induces mitochondrial fission, followed by its depolarization (Singh et al, 2010).…”
Section: Introductionmentioning
confidence: 81%
“…The endogenous levels of RIG-I, cGAS, and TLR3 (but not of TLR4 and MAVS) were reduced by stable (HT-29 cells) or transient (THP1 cells) overexpression (for 4 hrs) of Flag-IRGM (Figure 3E and 3F). Previously, we have shown that IRGM does not affect the expression levels of NLRC4 and AIM2 (Mehto et al, 2019). Since cGAS, RIG-I, and TLR3 expression is controlled by IFN response, the reduction of endogenous levels of these proteins could be an indirect effect of IRGM-mediated suppression of IFN response.…”
Section: Irgm Interacts and Degrades Nucleic Acid Sensor Proteins Tomentioning
confidence: 90%
See 3 more Smart Citations